Ultrafine clarithromycin nanoparticles via anti-solvent precipitation in subcritical water: Effect of operating parameters - Pu, Y.; Wen, X.; Li, Y.; Wang, D.; Foster, Neil; Chen, J. (Elsevier, 2017)
© 2016 Elsevier B.V. Clarithromycin (CLA) is an important drug used to treat various bacterial infections, while its effective bioavailability is limited by the poor water-solubility of the CLA molecule. Subcritical water (SBCW) processes have been demonstrated to be a new promising alternative for the preparation of drug nanoparticles with enhanced dissolution rate. In this work, we reported ultrafine CLA nanoparticles via anti-solvent precipitation in subcritical water, with detailed studies on the effects of operating parameters. The corresponding particle morphology, and dissolution rate properties of the CLA nanoparticles were characterized through scanning electronic microscopy (SEM), Fourier transform infrared spectrophotometry (FT-IR), powder X-ray diffraction (XRD) and dissolution tests. Under optimized experimental conditions, which was using 1.5 mL of SBCW at 150 °C as the solvent and 15 of aqueous PVP solution (0.4 wt%) as the anti-solvent, uniform sub-50 nm sized CLA nanoparticles are obtained. According to the dissolution testing, the ultrafine CLA nanoparticles exhibit very high dissolution rate (over 85% at 60 min) compared with that of raw CLA (10% at 60 min). Our results suggest that as-synthesized ultrafine CLA nanoparticles via anti-solvent precipitation in subcritical water are promising for efficient therapy.